Stability Assessment of Drill Ship Using Probabilistic Damage Stability Analysis - Mohan, Poonam; Shashikala, A.P. (Transactions on Maritime Science, 2019)
Drill ship is a ship-shaped structure with a drilling unit at its center and with oil compartments, which is moored and kept in position using anchors. These ships should be capable of working in deep sea for a long time, hence affected by harsh ocean environment. Drill units are said to have greater heave motion, and the height of the derrick influences the vessel’s stability. MARPOL Oil Outflow Analysis is performed for damaged crude oil carriers or tankers and Mobile offshore drilling units (MODU) in damaged condition. In the present study, probabilistic analysis is performed on drill ship to understand its stability behavior under damaged condition. Stability assessments are carried out by considering single and multiple damage locations. Oil outflow analysis is carried out for different damage cases of oil tank. Probabilistic damage assessment is done for load cases up to 50% flooding, to obtain stability charts. These charts will be useful to understand variations in stability parameters under damaged conditions.